Peningkatan Kemampuan Guru Dalam Menerapkan Model Pembelajaran Student Teams Achievement Division (STAD) di MTs Attaqwa 06 Bekasi - bin Abdul Hakim, Muhammad Kamal; Marzuq, Ahmad; Ilham, Andri (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
This community service activity aims to improve the ability of teachers in Bekasi, which is one of the FBS fostered areas, to apply the Student Teams Achievement Division (STAD) learning model. The outputs of this activity are: 1. Teachers in Bekasi who became participants received training on the Student Teams Achievement Division (STAD) learning model. 2. Teachers in Bekasi who participated in the training can apply the Student Teams Achievement Division (STAD) learning model in classroom learning.